2016
DOI: 10.3390/rs8110938
|View full text |Cite
|
Sign up to set email alerts
|

Data Service Platform for Sentinel-2 Surface Reflectance and Value-Added Products: System Use and Examples

Abstract: This technical note presents the first Sentinel-2 data service platform for obtaining atmospherically-corrected images and generating the corresponding value-added products for any land surface on Earth. Using the European Space Agency's (ESA) Sen2Cor algorithm, the platform processes ESA's Level-1C top-of-atmosphere reflectance to atmospherically-corrected bottom-of-atmosphere (BoA) reflectance (Level-2A). The processing runs on-demand, with a global coverage, on the Earth Observation Data Centre (EODC), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 26 publications
(39 reference statements)
5
99
0
Order By: Relevance
“…In some cases, correlation coefficients appear slightly lower for band 1, likely because of the lower spatial resolution (60 m for MSI). In general, however, the presented results are also in good agreement with the ones presented by Vuolo et al, [20], who found determination coefficients ranging from 0.90 to 0.96 for the six homologous bands (B1 was not considered). The performed tests highlight that one issue is the choice of the near-infrared band.…”
Section: Resultssupporting
confidence: 80%
“…In some cases, correlation coefficients appear slightly lower for band 1, likely because of the lower spatial resolution (60 m for MSI). In general, however, the presented results are also in good agreement with the ones presented by Vuolo et al, [20], who found determination coefficients ranging from 0.90 to 0.96 for the six homologous bands (B1 was not considered). The performed tests highlight that one issue is the choice of the near-infrared band.…”
Section: Resultssupporting
confidence: 80%
“…The results of the inter-comparison of official products were not unexpected, as the use of different radiometric correction codes, which are specifically adapted to each sensor, provided good outcomes for their corrected imagery, but not the best correlations between inter-sensor data. Vuolo et al [90] evaluated the Sen2Cor-SNAP and 6S-LaSRC coherence at six european test sites, obtaining an r 2 = 0.9, similar to the r 2 = 0.92 obtained in the present study. On the other hand, PIA-MiraMon showed a good inter-sensor correlation (r 2 = 0.96), providing robustly corrected data, because it is based on common radiometric areas.…”
Section: Discussionsupporting
confidence: 64%
“…Remote sensing is an effective tool for detecting damaged areas because it can be used to document damage to large areas without direct access to the affected area (Yamazaki and Matsuoka, 2007;Rathje and Adams, 2008;Dell'Acqua and Gamba, 2012). Immense improvement to the accessibility of remote-sensing imagery data and geospatial data processing tools has been achieved over the last several years (Vuolo et al, 2016;Korosov et al, 2016). A dramatic increase in the number of satellite, aircraft, and unmanned aerial vehicle (UAV) sensors has been observed as well.…”
Section: Introductionmentioning
confidence: 99%